IMPROVEMENT OF THE WEATHER CHANNEL OF THE AIRFIELD RADAR COMPLEX "DNEPR-A" - Pisa, D. M.; Chernoborodova, N. P.; Chernoborodov, M. P. (Radio Electronics, Computer Science, Control, 2024)
The analysis of technical solutions have been performed, when making a design of airfield radar complex (ARC) «Dnepr-A» weather channel, as well as of algorithms of processing weather data a source of which is target channel. There has been estimated efficiency of weather channel operation within the ARC development model. The ways of further enhancement of complex «Dnepr-A» weather channel were offered, new algorithms of eliminating an effect of underlying surface clutter have been approved.